2018
DOI: 10.3389/fimmu.2017.01988
|View full text |Cite
|
Sign up to set email alerts
|

NLRC4 Inflammasome-Driven Immunogenicity of a Recombinant MVA Mucosal Vaccine Encoding Flagellin

Abstract: Bacterial flagellin enhances innate and adaptive immune responses and is considered a promising adjuvant for the development of vaccines against infectious diseases and cancer. Antigen-presenting cells recognize flagellin with the extracellular TLR5 and the intracellular NLRC4 inflammasome-mediated pathway. The detailed cooperation of these innate pathways in the induction of the adaptive immune response following intranasal (i.n.) administration of a recombinant modified vaccinia virus Ankara (rMVA) vaccine e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…These findings are in agreement with observations of others identifying ovalbumin-specific IgA antibodies in the bronchoalveolar lavage fluid in mice intranasally immunized with MVA expressing ovalbumin ( 15 ). Others showed in non-human primates that aerosol immunization with recombinant MVA induced specific IgA in the genital tract ( 16 , 17 ) or T cells specific for the transgene in the lung ( 18 ).…”
Section: Mva and Baltsupporting
confidence: 93%
“…These findings are in agreement with observations of others identifying ovalbumin-specific IgA antibodies in the bronchoalveolar lavage fluid in mice intranasally immunized with MVA expressing ovalbumin ( 15 ). Others showed in non-human primates that aerosol immunization with recombinant MVA induced specific IgA in the genital tract ( 16 , 17 ) or T cells specific for the transgene in the lung ( 18 ).…”
Section: Mva and Baltsupporting
confidence: 93%
“…Pyroptosis is a proinflammatory reaction that induces programmed cell death and recognizes flagellin components to initiate the process. Researchers have found that flagellin triggers caspase 1-dependent activation of pyroptosis, which is mediated by TLR5 and the neuronal apoptosis inhibitory protein 5 (Naip5)/NLR family CARD domain-containing protein 4 (NLRC4) signaling pathway, to suppress breast cancer cell growth 10 . Additionally, the tumor suppressor p53 also modulates TLR signaling in cancer cells.…”
Section: Mechanisms Of Tlr Action In Cancer Therapymentioning
confidence: 99%
“…Vault NPs Large cytoplasmic ribonucleoprotein particles NLRP3 [32] Chitosan Biodegradable cationic polymer obtained from chitin NLRP3 [10,[33][34][35][36] Silica particles Biocompatible particles NLRP3 [37,38] Gold NPs Gold nanoparticles NLRP3 [39] Flagellin Used as recombinant protein, or encoded in virus replicon or DNA plasmid NLRC4 [40][41][42][43][44] DNA vaccines DNA plasmids or Aim2 encoded in vector as immunopotentiator AIM2 [45][46][47] CTB Cholera toxin B from Vibrio cholerae, added to an Ag, or as a DNA vaccine NLRP3, Pyrin [48][49][50] oxPAPC Oxidized 1-palmitoyl-2-arachidonoyl-snglycero-3-phosphorylcholine (generated during tissue damage)…”
Section: Description Targeted Inflammasome Referencesmentioning
confidence: 99%
“…Flagellin has also been assessed for adjuvanticity after administration of a recombinant modified vaccinia virus Ankara (rMVA) vaccine encoding the flagellin gene. Immunisation with rMVA-flagellin induced enhanced secretion of mucosal IL-1β and TNF-α, resulting in elevated T-cell and antibody responses, which were diminished in NLRC4 −/− mice [ 43 ]. Similarly, incorporating flagellin into the replicon of an alphavirus enhanced IgG1 and IgG2a/c titres, indicating an enhancement of Th1 and Th2 type responses.…”
Section: Experimental Adjuvants That Activate Inflammasomesmentioning
confidence: 99%